(untitled) (Journal of Research Updates in Polymer Science, 2019)
The nature of starting materials and the conditions of polyurethane (PU) preparation are regarded as the main general parameters that determine PU thermal resistance. The effect of structure and presence of additives were identified as the major general factors on this regard. Structural factors include phase microstructure, i.e. chemical structure, proportion and segregation of soft and hard segments); polyol type (petrochemical or natural oil-based); isocyanate and chain extender type and thermoplasticity of PU. Respect to the effect of additives, the incorporation of fillers is the most direct strategy to increase PU heat resistance. With respect to fiber additives, in general a positive effect is found on improving thermal resistance, although this generalization could not apply, considering the large number of different PU and environmental conditions of usage.